2012
DOI: 10.1021/jp306124n
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Light Trapping Efficiency of Plasmonic Polymer Solar Cells through Photon Management

Abstract: In this study, we have explored how light trapping efficiency can be enhanced by using gold nanoparticles (Au NPs) of various sizes and shapes on the front of polymer solar cells (PSCs) with the active layerblends of poly(3-hexyl thiophene) and [6,6]-phenyl-C 61 -butyric acid methyl ester. The light-concentrating behavior was enhanced after we had incorporated gold nanospheres or nanorods into the anodic buffer layer [based on poly (3,4-ethylenedioxythiophene):polystyrenesulfonate] to trigger various localize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
107
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(112 citation statements)
references
References 33 publications
0
107
0
Order By: Relevance
“…10 Notably, compared to the relatively small shi in PEDOT:PSS (l res ¼ 542 nm), the resonance position reached 750 nm with an increased extinction cross-section in the whole 500-800 nm range when doping the Au NPs in the PTB7/PC 71 BM blend. The large wavelength shi led to a signicantly more matched spectral overlap between the resonance wavelength and the absorption of the photoactive material (PTB7, with absorption range of 500-750 nm), 17,[43][44][45][46] suggesting an advantage if the 20 nm Au NPs can be incorporated in the active layer. The near-eld distributions of a 20 nm Au NP in different environments at the corresponding resonance wavelengths (water, l res ¼ 523 nm; PEDOT:PSS, l res ¼ 542 nm; PTB7/PC 71 BM blend, l res ¼ 750 nm) are shown in Fig.…”
mentioning
confidence: 99%
“…10 Notably, compared to the relatively small shi in PEDOT:PSS (l res ¼ 542 nm), the resonance position reached 750 nm with an increased extinction cross-section in the whole 500-800 nm range when doping the Au NPs in the PTB7/PC 71 BM blend. The large wavelength shi led to a signicantly more matched spectral overlap between the resonance wavelength and the absorption of the photoactive material (PTB7, with absorption range of 500-750 nm), 17,[43][44][45][46] suggesting an advantage if the 20 nm Au NPs can be incorporated in the active layer. The near-eld distributions of a 20 nm Au NP in different environments at the corresponding resonance wavelengths (water, l res ¼ 523 nm; PEDOT:PSS, l res ¼ 542 nm; PTB7/PC 71 BM blend, l res ¼ 750 nm) are shown in Fig.…”
mentioning
confidence: 99%
“…Although the surface plasmon resonance (SPR) in spherical metallic nanoparticles has been known for over one century, SPR-induced local electric field enhancement in the visible and near-infrared region has received increasing attention in recent years owing to the improved preparation method of metallic nanoparticles with complicated geometry and many promising applications. 1,2 Because of the interaction between incident electromagnetic field and SPR, the oscillating free electrons induced polarized electronic field has been greatly enhanced and could be used in surfaceenhanced Raman scattering (SERS), 3 surface enhanced fluorescence (SEF), 4,5 light trapping in solar cells, 6 and nonlinear optical response (NLO) including second harmonic generation, 7 third-order optical nonlinear effect, 8 optical limiting, 9 and optical bistability. 10 In order to obtain great enhancement of the local or near electric field, many experimental and theoretical efforts have been developed to study the local field enhancement of metallic nanoparticles with various shape and structure, such as nanorod, 11 nanoprism, 12 nanocube, 13 nanoshell, 14 and nanotube.…”
mentioning
confidence: 99%
“…That means that the resonance peaks of $ 575 and $ 770 nm in aqueous solution will move to $ 615 and $825 nm in the film, respectively, covering not only the whole absorption band of PTB7: PC 71 BM, but also its cutoff edge at $ 800 nm. According to Hsiao's analysis [35], our mixed NPs will result in an effective absorption increase in the active layer and thereby an improvement in solar cell performance.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, Li et al [22] used dual plasmonic nanostructures of 750 nm Ag nanogratings and 50 nm Au NPs to broaden active layer's absorption region and obtained a PCE of 8.79 70.15% with a $ 16% enhancement from 7.59 70.08%. In another work, Hsiao et al [35] combined Au nanospheres (NSs) with nanorods (NRs) which resulted in two resonant peaks with the absorption ranging from visible to near infrared (NIR) region. Through systematic analysis on film's extinction and photoluminescence (PL) spectra, they concluded that the integration of two types of Au NPs with the absorption edges covering the whole absorption spectrum is exceptionally beneficial to the performance improvements of OPVs.…”
Section: Introductionmentioning
confidence: 99%